O Programa Habitacional PER e o desenho de um projeto: Conjunto Habitacional Bairro Mineiro, Gondomar - Lígia Maria Teixeira Rodrigues (2020)
The present document arises from an awareness already acquired over the years, that housing is an essential "asset" that everyone should be entitled to regardless of their social strata. With a theoretical development on the concept of Neighborhood Unit, which is defined by a set of characteristics that I consider fundamental for the proper functioning of the group, it is highlighted and presented by a reflection on a qualitative design. Various residential solutions are evaluated, firstly carrying out an adequate study of the space design, presenting more recurrent and well-known solutions, reinforcing the need to valorise the outer space, its neighborhood structuring design, which generates coexistence, with a ecological balance privileging the urban green space with an investment of greater care with the common circulation and promotion of the pedestrian, considering ways of living and appropriation, with an inclusive design before the most fragile age group, namely children and the seniors. This analysis will have as purpose the study of PER Bairro Mineiro, as one of the examples of a program considered innovative and with a great variety of enterprises, having been the program that had the best result in solving the urban problem, clandestine neighborhoods. The design of the neighborhood reflects a history and culture from Minas Gerais that is prevalent throughout the territory, influenced by a design of Portuguese modernism by the architect José Carlos Loureiro, developed by a large-scale human intervention, guaranteed by one with low-floor buildings , with characteristics similar to workers' houses, from which the public space is valued and its transposition to the more private space.